PERAN GURU DALAM MEMBENTUK KARAKTER SISWA BERBASIS AJARAN ISLAM - Isnaini, Muthi’ah Syifa; Syahfitri, Khairani (Proceeding International Seminar of Islamic Studies, 2024)
This reseach aims to explore the role of teachers in foming character students based on Islamic teachings. The reseach method used involvesliterature analysis, studies, cases, and classroom observation. The research findings highlightthe importance of a holistic approach that involves academic learning and Islamic moral values.Teachers are identified as key agents who encourage student character development through a pedagogical approach that emphasizes ethics, integrity and social concerm. It is hoped that the result of this research can contribute to further understanding of how the implementation of Islamic teachings in education can strengthen the role of teachers in education. It can strengthen the role of teachers in shaping students character as a whole. In this research,teacher are not only transmitter of knowledge, but also have responsibilities.Responsible for guiding and developing student moral and spiritual character with Islamic values. This research explore teaching strategis that are centered on Islamic values, as well as teacher-student intteractions that strengthen character formation. By involving case studies and qualitative analysis, this research provides in-depth insight into how teachers can play a key role in developing student character based on Islamic teachings, creating a holistic and athical education environment.